1999
DOI: 10.1159/000055519
|View full text |Cite
|
Sign up to set email alerts
|

An Index for Human Lens Transparency Related to Age and Lens Layer: Comparison between Normal Volunteers and Diabetic Patients with Still Clear Lenses

Abstract: Objective: The light scattering intensity of normal, clear lenses varies with age and with the localization within the lens. Realizing the biometry of single lens areas together with their relevant light scattering intensity one should be able to calculate an index to express the lens transparency properties of normal human lenses in dependence on age. Performing the same procedure in cases of diabetic patients with still clear lenses it should become possible to obtain an index for the lens transparency prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 11 publications
0
20
0
3
Order By: Relevance
“…Diabetics are known to have thicker lenses. [6][7][8]16 Therefore, to remove the confounding effect of diabetes on lens thickness, diabetics were excluded. Peripheral cortical spokes can be missed in the non-dilated pupil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetics are known to have thicker lenses. [6][7][8]16 Therefore, to remove the confounding effect of diabetes on lens thickness, diabetics were excluded. Peripheral cortical spokes can be missed in the non-dilated pupil.…”
Section: Discussionmentioning
confidence: 99%
“…3 The thickness of the human lens has been found to be related to age, sex, cataract type, and diabetic status. [4][5][6][7][8][9] The primary objective of our observational study was to compare lens thickness measurements in eyes with a clear lens to eyes with different types of isolated cataract (nuclear, cortical, and posterior subcapsular (PSC)); the influence of age groups and axial length (AL) categories on lens thickness; and the impact of lens thickness on anterior chamber depth (ACD) in individuals with cataract and clear lens.…”
Section: Introductionmentioning
confidence: 99%
“…However, an older lens has a greater tendency to scatter light, even if it is clear. 21 This could affect the test results when using reduced stimulus luminance.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study has already shown a very high correlation (r = 0.91) between L2 and the full lens thickness [12]. eyes.…”
Section: Resultsmentioning
confidence: 72%
“…The correlation is quite good with r = 0.91 [12]. It is possible to substitute L2 for full lens thickness at least in the transparent crystalline lens.…”
Section: Discussionmentioning
confidence: 86%